Leaf Epidermis: The Ambiguous Symplastic Domain - Voitsekhovskaja, Olga V.; Melnikova, Anna N.; Demchenko, Kirill N.; Ivanova, Alexandra N.; Dmitrieva, Valeria A.; Maksimova, Anastasiia I.; Lohaus, Gertrud; Tomos, A. Deri; Tyutereva, Elena V.; Koroleva, Olga A. (Frontiers in Plant Science, 2021)
The ability to develop secondary (post-cytokinetic) plasmodesmata (PD) is an important evolutionary advantage that helps creating symplastic domains within the plant body. Developmental regulation of secondary PD formation is not completely understood. In flowering plants, exclusively secondary PD occur between cells from different lineages, e.g. at the L1/L2 interface within shoot apices, or between leaf epidermis (L1-derivative) and mesophyll (L2-derivative). However, the highest numbers of secondary PD occur in leaf minor veins between bundle sheath cells and phloem companion cells in a group of plant species designated ‘symplastic’ phloem loaders, as opposite to ‘apoplastic’ loaders. This poses a question of whether secondary PD formation is upregulated in general in symplastic loaders. Distribution of PD in leaves and in shoot apices of two symplastic phloem loaders, Alonsoa meridionalis and Asarina barclaiana, was compared with that in two apoplastic loaders, Solanum tuberosum (potato) and Hordeum vulgare (barley), using immunolabelling of the PD-specific proteins and TEM, respectively. Single-cell sampling was performed to correlate sugar allocation between leaf epidermis and mesophyll to PD abundance. Although the distribution of PD in the leaf lamina (except within the vascular tissues) and in the meristem layers was similar in all species examined, far fewer PD were found at the epidermis/epidermis and mesophyll/epidermis boundaries in apoplastic loaders compared to symplastic loaders. In the latter, the leaf epidermis accumulated sugars, suggesting sugar import from the mesophyll via PD. Thus, leaf epidermis and mesophyll might represent a single symplastic domain in Alonsoa meridionalis and Asarina barclaiana.